HUBUNGAN PENERAPAN PROGRAM KESELAMATAN KERJA DENGAN TINDAKAN TIDAK AMAN PADA KARYAWAN PT PERKEBUNANNUSANTARA IV UNIT BAH BUTONG KABUPATEN SIMALUNGUN TAHUN 2013 - Evia Dessy manurung; Halinda Sari Lubis; Lina Tarigan (Lingkungan dan Kesehatan Kerja, 2014)
Unsafe acts still present in PT Perkebunan Nusantara IV Unit Bah Butong altough safety program like procedures works, risk management and exposure to hazards has implementation. The aim of the study was to determine the relationship implementation of safety programs with unsafe action on workers PT Perkebunan Nusantara IV Unit Usaha Teh Bah Butong in 2013. Design this research is cross sectional,  and sampel are 65 people. Analysis of the data used is univariat. The results showed that unsafe acts by employees of PT Perkebunan Nusantara IV Unit Usaha Teh Bah Butong of 65 respondents who are at risk of moderate (Moderate Risk) as many as 23 employees using defective tools, 21 employees were not wearing PPE, 16 employees make improvements when the engine is running , 15 employees redundant load something, 11 employees put something out of place, 5 employees redundant lifting weights, 5 employees perform any work position, 3 employees released safety device and 1 employee receive call while working. Based on the results of the study are expected to SMK3 parts to improve its supervision of production employees. Keywords :    Implementation of Safety Program, Unsafe Act